2019
DOI: 10.1016/j.apergo.2019.102902
|View full text |Cite
|
Sign up to set email alerts
|

Comfortable seating: The influence of seating comfort and acoustic comfort on customers’ experience of hospitality in a self-service restaurant

Abstract: Does comfort in a restaurant influence people's experienced hospitality? Effects of seating comfort and acoustic comfort on the experience of hospitality were examined by means of a 2 x 2 between subjects experiment among 262 customers of a self-service restaurant, using the EH-scale measuring the experiential factors care, comfort and inviting. In line with theory on embodiment, MANOVA and mediation analysis showed that comfortable seating positively influences mental comfort, which subsequently increases the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(52 reference statements)
0
7
0
1
Order By: Relevance
“…Seating comfort is one of the most important indicators of automotive seat performance [1][2][3]. Around the world, there have been many studies on seating comfort, including car seats, truck seats [4], and bus and train seats [5].…”
Section: Introductionmentioning
confidence: 99%
“…Seating comfort is one of the most important indicators of automotive seat performance [1][2][3]. Around the world, there have been many studies on seating comfort, including car seats, truck seats [4], and bus and train seats [5].…”
Section: Introductionmentioning
confidence: 99%
“…At the one hand, high noise levels may cause discomfort because of the high cognitive load. This was the effect we expected but did not find (Chapter 6, Pijls et al, 2019), probably because the sound levels were not uncomfortable enough. On the other hand, low acoustic privacy may also cause physical discomfort during privacy-sensitive conversations because of the absence of background noise or the absence of a soundproof room.…”
Section: Environmental Service Cues Promoting Comfortmentioning
confidence: 52%
“…Furthermore, the experiential factor comfort may be related to the embodied concept of comfort; physical comfort is expected to activate mental comfort, which subsequently leads to the experience of hospitality. An experimental study in a self-service restaurant on the role of seating comfort and acoustic comfort showed that comfortable seating indeed triggered mental comfort, which in turn increased the comfort factor of the experience of hospitality (Pijls, Galetzka, Groen, & Pruyn, 2019). Thus, for both the care factor and the comfort factor of the experience of hospitality embodied cognition seems to play a role.…”
Section: Hospitality and Embodimentmentioning
confidence: 98%
See 2 more Smart Citations